Analisis Penyerapan Anggaran Berdasarkan Jenis Belanja Di Badan Standardisasi Nasional - One Agus Sukarno (Jurnal Manajemen Bisnis Krisnadwipayana, 2026)
Budget absorption is an important indicator in assessing the effectiveness of fiscal policy implementation and the quality of state financial management. An optimal absorption rate reflects the ability of government institutions to implement programs and activities according to established plans. This study aims to analyze the influence of personnel expenditures, goods expenditures, and capital expenditures on the level of budget absorption at the National Standardization Agency (BSN) during the 2010–2024 period. The study uses a quantitative approach with secondary data sourced from budget realization reports and official BSN financial documents. The dependent variable in this study is budget absorption, measured by the ratio of realization to the budget ceiling in percentage, while the independent variables include the realization of personnel expenditures, goods expenditures, and capital expenditures, transformed into natural logarithms (LN). The analysis technique used was multiple linear regression, with a classical assumption test first conducted to ensure model feasibility. The results show that personnel expenditures have a significant effect on budget absorption, while goods expenditures and capital expenditures do not have a significant effect on budget absorption at BSN. However, simultaneously, the variables of personnel expenditures, goods expenditures, and capital expenditures influence budget absorption.